The rise of invariability in the Low Lithuanian reflexive participles and verbal nouns - Petit, Daniel (Baltistica, 2014)
In the Low Lithuanian dialects reflexive half-participles and verbal nouns are indeclinable and display a unique ending -damos, resp. -imos. The aim of this paper is to explain the invariability of these forms, which represents a striking feature of Low Lithuanian. It is proposed that invariability in the verbal nouns in -imos derives from their neuter origin, whereas in the half-participles in -damos it results from complex processes of phonological merging. In both cases, the preservation of invariability is due to the overall difficulty of building reflexive nominal forms of the verbs.
Keywords: Lithuanian; Žemaitian; dialectology; historical morphology; reflexive participles; verbal nouns; invariability; -damos; -damas; -imas